Feedback solutions in rowing training - Sorysz, J.; Loerakker, M. B.; Eska, B. (UbiComp '24: Companion of the 2024 on ACM International Joint Conference on Pervasive and Ubiquitous Computing, 2024)
The growing accessibility of wearables for sports encourages people to track their training progress and health information while exercising. The recorded information provides insights into the body and forms the basis for feedback systems. Though requirements for the feedback design vary greatly depending on the type of sport. Especially for activities involving the whole body, such as rowing. It trains strength and endurance, does not place excessive stress on leg joints, yet involves coordinating multiple muscles simultaneously, making it a complex sport by combining it all at once. In this paper, we look into research on feedback modalities and review the advantages and disadvantages of feedback examples in Human-Computer Interaction focusing on the rowing context.